Synthetic inhibitors of galectin-1 and -3 selectively modulate homotypic cell aggregation and tumor cell apoptosis - Iurisci, Ida (2009)
Galectins have emerged as critical regulators of tumor progression and metastasis, by modulating different biological events including homotypic cell aggregation, apoptosis, migration, angiogenesis and immune escape. Therefore, galectin inhibitors might represent novel therapeutic agents for cancer. A series of structural analogs of the disaccharide methyl beta-lactosaminide were screened as potential galectin inhibitors by examining their capability to block binding of galectin-1 and/or galectin-3 to LGalS3BP in solid-phase assays. To demonstrate any functional role in vitro, oligosaccharides were characterized by their ability to regulate tumor cell apoptosis and LGalS3BP-induced homotypic cell aggregation.